Ocular blood flow levels and visual prognosis in a patient with nonischemic type central retinal vein occlusion - Kimihito Maeda (Dove Medical Press, 2009)
Kimihito Maeda, Futoshi Ishikawa, Hiroshi OhguroDepartment of Ophthalmology, Sapporo Medical University, School of Medicine, Sapporo, JapanAbstract: We look at the case of a 39-year-old female patient suffering from a sudden decrease in her left visual acuity (0.08). Her macular edema was examined using optical coherence tomography, and her optic disc blood flow was examined with laser speckle flowgraphy (LSFG). Additionally, the degree of seriousness of the central vein occlusion was evaluated through fluorescein angiography (FA). Ocular fundus findings revealed central vein occlusion associated with macular edema, and FA determined her disease type as a nonischemic-central vein occlusion. Daily doses of 100 mg of aspirin were administered orally to the patient. Upon administration, her ocular blood flow almost immediately increased. In this study, we demonstrate the potential of LSFG as a means to investigate ocular blood flow.Keywords: ocular blood flow, nonischemic central retinal vein occlusion, laser speckle flowgraphy